2018
DOI: 10.1007/978-3-319-90530-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Grammar-Based Compression of Unranked Trees

Abstract: We introduce forest straight-line programs (FSLPs) as a compressed representation of unranked ordered node-labelled trees. FSLPs are based on the operations of forest algebra and generalize tree straight-line programs. We compare the succinctness of FSLPs with two other compression schemes for unranked trees: top dags and tree straight-line programs of firstchild/next sibling encodings. Efficient translations between these formalisms are provided. Finally, we show that equality of unranked trees in the setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In [17] it was shown that from a top dag G one can compute in linear time an equivalent FSLP of size O(|G|). Vice versa, from an FSLP H for a tree t ∈ C a (for some a ∈ Σ) one can compute in time O(|Σ| · |H|) an equivalent top dag of size O(|Σ| · |H|).…”
Section: Cluster Algebras and Top Dagsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [17] it was shown that from a top dag G one can compute in linear time an equivalent FSLP of size O(|G|). Vice versa, from an FSLP H for a tree t ∈ C a (for some a ∈ Σ) one can compute in time O(|Σ| · |H|) an equivalent top dag of size O(|Σ| · |H|).…”
Section: Cluster Algebras and Top Dagsmentioning
confidence: 99%
“…Vice versa, from an FSLP H for a tree t ∈ C a (for some a ∈ Σ) one can compute in time O(|Σ| · |H|) an equivalent top dag of size O(|Σ| · |H|). The additional factor |Σ| in the transformation from FSLPs to top dags is unavoidable; see [17] for an example. Proof.…”
Section: Cluster Algebras and Top Dagsmentioning
confidence: 99%
See 3 more Smart Citations